Inclusão obrigatória da história e cultura africana, afro-brasileira e indígena no currículo oficial: vozes e tensões no projeto curricular do estado de Pernambuco - Marinho, Geonara Marisa de Souza (2014)
The object of this study is the reinterpretation on the Laws 10.639/03 and 11.645/08 by teachers; both laws govern the mandatory inclusion in the official curriculum of African, Afro-Brazilian and indigenous history and culture in basic education schools in the State of Pernambuco. Thus, in the study we aim to understand how has been happening the process of reinterpretation in basic education of the Laws in the State of Pernambuco since 2003. The specific research objectives were: analyze the pedagogical proposal from state schools of Pernambuco, with reference to the legal requirement for inclusion the themes on the agenda in the official curriculum; and understand how teacher‟s pedagogical practice contributes to Laws realization. From theoretical and methodological procedures of the sociology of absences, emergencies and translation work (SANTOS, 2007, 2008, 2010), we analyzed the speech of teachers, managers and those who constitute the government discourse about this topic inclusion. We started by the assumption that the process of invisibility which blacks and indigenous people are subjected, which in the Brazil‟s social, political, cultural and economic formation process, for centuries was marked by a colonial system of exploitation which marginalized the knowledge and experiences perpetrated by these people, being urgent a project of curriculum restructuring to leverage the black and indigenous history and culture in the official school curriculum. The theoretical-methodological approach is also comprised of the following categories of analysis: cultural differences and incompleteness, and equality, with investments in Santos (2007, 2008, 2010); curriculum (GIROUX, 1986, 1999); Apple (2008, 2011); Arroyo (2007, 2011) and Freire‟s dialogue (1980, 1981, 1987, 1996, 2003, 2012). The study point to the necessary awareness of those involved in educational practice and in the formation of teachers, both initial as continuing, to work with the themes proposed by the Law in connection with the execution of an intercultural dialogue based on equality and recognition of difference. The research also points the necessary questioning of some issues, such as inter-knowledge, self-knowledge and self-education, so that this triad happen within the counter-hegemonic globalization through a network of interactions that promote knowledge and critique appreciation of cultural and historical diversity of practices and knowledge of different subjects, thus enhancing mutual understanding and making possible coalitions and joint collective actions. The constant dialogue with different knowledge fosters the emergence of alternative sources, in view of the configuration of an ecology of knowledge and objective emancipatory social transformation